PENGARUH PENGENDALIAN INTERNAL PENERIMAAN DAN PENGELUARAN KAS TERHADAP KECURANGAN AKUNTANSI PADA PT. NAGA HARI UTAMA MEDAN - Syaharman . (Universitas Islam Islam Sumatera Utara, 2021)
The purpose of this study is to find out the influence of internal controls on accounting fraud that occurs in the company. If the internal control of a company is weak then the possibility of errors and fraud is greater. Conversely, if the internal controls are strong, then the possibility of fraud can be reduced. The effectiveness of internal control has a great influence in efforts to prevent the tendency of accounting fraud, with internal control, checking will occur automatically on one's work by others. The instruments used in this study are closed questionnaires, the questionnaires used are to net data on internal control of cash receipts and internal control of each respondent's cash expenditure against accounting fraud. Data collection is used by running a questionnaire containing questions that have been prepared in advance and answers related to research problems. The results of the study obtained and at the same time the conclusion of this study include that from the results of the evaluation in adjusted R Square number 0.641, this means that 64.1% of the variation in accounting fraud can be influenced by internal control factors of cash receipts and internal control of cash expenditures, while 35.9% is influenced by other factors. From the results of the simultaneous test obtained seen Fhitung value of 44,776 Ftabel 3.18 with a significant level of 0.000 0.05, it can be concluded that the hypothesis (H1) can be accepted, namely internal control of cash receipts and internal control of cash expenditures together positively and significantly on accounting fraud at PT. Naga Hari Utama Medan. On the partial test the effect of internal control of cash receipts on accounting fraud obtained the value of t-calculate = 9,443 t-table 2,000 with a significant 0.000 0.005, it was concluded ho was rejected and H1 received, which means internal control of cash receipts positively and significantly partially on accounting fraud. Furthermore, the results of partial testing of the effect of internal control of cash expenditures against accounting fraud obtained a value of t-calculate = 2,858 t-table 2,000 with a significant 0.000 0.005, then concluded Ho was rejected and H1 received, which means internal control of cash expenditures positively and significantly partially on accounting fraud at PT. Naga Hari Utama Medan.